Pengembangan Aplikasi Pengenalan Objek Wisata di Pulau Buton Berbasis Augmented Reality - Hamsinar, Henny; Suryawan, Mohammad Arif; Arsi, Arsi (JURNAL INFORMATIKA, 2025)
Tourism is a strategic sector that significantly contributes to regional economic development, including in the Buton Island area, which offers numerous potential tourist attractions. However, tourism promotion in this region still faces challenges, particularly due to the limitations of conventional information media such as brochures, printed maps, and static websites that lack interactivity and fail to meet the expectations of modern tourists seeking accessible, engaging, and dynamic information. This condition highlights the need for innovative promotional media capable of delivering attractive content and increasing user engagement. Augmented Reality (AR) offers a promising solution, as it integrates real-world objects with interactive digital elements, thereby creating a more immersive informational experience. This study aims to design and develop an Augmented Reality–based application for introducing tourist attractions on Buton Island as an alternative information medium for visitors. The research employed a qualitative approach through interviews with officers from the Tourism Departments of Baubau City, Buton Regency, South Buton, Central Buton, North Buton, and Wakatobi, as well as direct observations of tourism managers to identify on-site needs and issues. A literature review was also conducted to examine relevant theories and best practices regarding AR application development. The results indicate that the developed AR application operated effectively on three tested smartphone devices and successfully detected markers at distances of 10–100 cm. The application was considered useful in providing tourism information, enhancing visitors’ knowledge, and presenting images and descriptions of attractions interactively.